National fiscal stimulus packages and consolidation strategies in a monetary union - Christoph Bierbrauer (Osnabrück University, Institute of Empirical Economic Research, 2017)
We present a two-country New Open Economy Macroeconomics model of a currency union featuring an overlapping generations structure of the Blanchard (1985)-Yaari (1965) type as well as monopolistic frictions and staggered adjustment in the goods and labor market. We allow for public investment and distortionary taxation. We study the effects of fiscal policy measures such as public spending, tax cuts targeted to households and public investment as suggested by the Euro- pean Commission (2008). In particular, we explore the effects of fiscal policy as a function of the financing decision of the implementing government. We find that the impact of fiscal measures on national variables as well as the spillovers depend on the assumed degree of household myopia and again, the financing decision of the government. However, the introduction of a complex fiscal sector which enables the government to choose between alternative financing schemes is an important determinant of the effects of fiscal expansions on key macroeconomic variables such as, output and consumptions. Thus, modeling a complex fiscal sector on both sides of the budgets is crucial for the results and therefore the effectiveness of fiscal stimulus packages.
Keywords: E62; F33; F41; H31; H50; H63; 330; Overlapping generations; New open economy macroeconomics; Public Debt; Decentralized fiscal policy; Monetary union